Reviewing Law Enforcement on Small and Medium Enterprise Partnerships in Indonesia from a Competition Law Perspective - Anita Afriana; Efa Laela Fakhriah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Micro, small, and medium enterprises (MSMEs) play a crucial role in the economic development of Indonesia. One activity MSMEs can engage in is forming partnerships. These partnerships are established through innominate contracts, which, in principle, constitute partnership agreements. The Business Competition Supervision Commission, or Komisi Pengawasan Persaingan Usaha (KPPU), holds the authority to oversee both the formation and performance of partnership agreements entered into by MSMEs. This article uses a normative juridical approach with qualitative data to evaluate the supervisory role of KPPU in overseeing the performance of partnership agreements and the amicable settlement of disputes through changes in behavior under competition law. The results conclude that KPPU oversees compliance with the agreements and performance in accordance with general contractual principles, specifically those that must be included in partnership agreements. KPPU’s supervision, as part of law enforcement, occurs in two phases: the preliminary stage and the subsequent stage. In the subsequent stage, KPPU may impose administrative sanctions and criminal compensation based on the material facts of the proceedings. If the reported party changes their behavior during the preliminary stage, the proceeding may be terminated, allowing the dispute to be settled amicably. This approach should be prioritized as part of restorative justice, as it emphasizes law enforcement focused on restoring the original state and reestablishing harmonious relationships within society.